Directed Evolution of a Mycobacteriophage - María Cebriá-Mendoza; Rafael Sanjuán; Pilar Domingo-Calap (MDPI AG, 2019)
Bacteriophages represent an alternative strategy to combat pathogenic bacteria. Currently, Mycobacterium tuberculosis infections constitute a major public health problem due to extensive antibiotic resistance in some strains. Using a non-pathogenic species of the same genus as an experimental model, Mycobacterium smegmatis, here we have set up a basic methodology for mycobacteriophage growth and we have explored directed evolution as a tool for increasing phage infectivity and lytic activity. We demonstrate mycobacteriophage adaptation to its host under different conditions. Directed evolution could be used for the development of future phage therapy applications against mycobacteria.